The Ways of Forming Secondary Nomination in Uzbek Language and Its Impact on Linguistics - Ikramboyevna, Axmedova Dilrabo; Ikramboyevna, Sattarova Dildora (European Journal of Life Safety and Stability (2660-9630), 2021)
This article investigates the role of secondary nomination in modern Uzbek language hence it encompasses information about nomination, ways of forming secondary nomination and its impact on both speaker and receiver. Aside from that, it provides illustrations which maintain in detail how secondary nomination is formed as well as interpreted.